Realizing the right to food in South Asia - Pradeep Bhargava; Manju Balana (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Basic human rights recognize the intrinsic value of freedom, only not for the value of freedom itself, but also for its instrumental role enabling an individual to choose a bundle of commodities and wellbeing. The role of food, a basic necessity of life, in fostering freedom is important, to say the least. South Asian countries have witnessed a substantial increase in food production but nutritional emergency prevails in large regions indicating both failure in food distribution and the lack of capacity to acquire food. Acquiring food is intrinsically related to the availability of work, and people's capacity to undertake work. This paper surveys the initiatives by the state and civil society in South Asia for ensuring the right of the individual to acquire food, and for that purpose to be able to work and earn. It is argued that in order to ensure the right to food would require not only food and work programmes, but also attitudinal changes in the authorities. Authorities need to consider themselves as duty bearers—not patrons or benevolent lords—so that the civil society can ensure the political freedom of the people to scrutinize the action of governments.
Keywords: Q18; O13; R58; N55; 330; human rights; state; civil society; food; South Asia; Menschenrechte; Ernährung